Molecular Biology and Infection of Hepatitis E Virus - Nan, Yuchen; Zhang, Yan-Jin (Frontiers in Microbiology, 2016)
Hepatitis E virus (HEV) is a viral pathogen transmitted primarily via fecal-oral route. In humans, HEV mainly causes acute hepatitis and is responsible for large outbreaks of hepatitis across the world. The case fatality rate of HEV-induced hepatitis ranges from 0.5 to 3% in young adults and up to 30% in infected pregnant women. HEV strains infecting humans are classified into four genotypes. HEV strains from genotype 3 and 4 are zoonotic, whereas those from genotype 1 and 2 have no known animal reservoirs. Recently, notable progress has been accomplished for better understanding of HEV biology and infection, such as chronic HEV infection, in vitro cell culture system, quasi-enveloped HEV virions, functions of the HEV proteins, mechanism of HEV antagonizing host innate immunity, HEV pathogenesis and vaccine development. However, further investigation on the cross-species HEV infection, host tropism, vaccine efficacy and HEV-specific antiviral strategy is still needed. This review mainly focuses on molecular biology and infection of HEV and offers perspective new insight of this enigmatic virus.